The 1st International Electronic Conference on Microbiology 2021
DOI: 10.3390/proceedings2020066020
|View full text |Cite
|
Sign up to set email alerts
|

Allium cepa L. Inoculation with a Consortium of Plant Growth-Promoting Bacteria: Effects on Plant Growth and Development and Soil Fertility Status and Microbial Community

Abstract: The present work was aimed at investigating the effects of a four strains consortium—Azospirillum brasilense, Gluconacetobacter diazotrophicus, Herbaspirillum seropedicae, and Burkholderia ambifaria—on crops of Allium cepa L. and its soil health. The bacterial consortium was inoculated on seeds of two different onion varieties; inoculated seeds and control ones (treated with autoclaved inoculum) were sown in open-field and followed until harvest. Plant growth development parameters, as well as soil physico-che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…PGPR formulations are a significant biostimulant class, as they allow root growth, mineral availability, and efficiencies in the utilization of nutrients in the crop rhizosphere to increase crop growth [45]. Many PGPR are known to stimulate phytohormone production through a combination of various mechanisms [46][47][48][49][50][51][52][53] represented in Table 2.…”
Section: Plant Growth Promotion and Nutrient Acquisitionmentioning
confidence: 99%
“…PGPR formulations are a significant biostimulant class, as they allow root growth, mineral availability, and efficiencies in the utilization of nutrients in the crop rhizosphere to increase crop growth [45]. Many PGPR are known to stimulate phytohormone production through a combination of various mechanisms [46][47][48][49][50][51][52][53] represented in Table 2.…”
Section: Plant Growth Promotion and Nutrient Acquisitionmentioning
confidence: 99%
“…Various notable protective mechanisms in the utilization of microbial biostimulants under different stresses are osmolite production, phytohormone level modulation, increased antioxidant activity, and secretion of extracellular polymeric substances (EPS) under water stress such as flooding and drought [129][130][131]; phytohormone level modulation, emission of volatile organic components, ice nucleation activity antagonism, delay of senescence, and osmo and thermal protection under thermal stress such as freezing and extreme heat [132][133][134][135]; increased soil exploration and mineral nutrient solubilization under nutrient stress [136,137]; and induced system resistance, direct antagonism with pathogens, and phytohormone level modulation under biotic stress [138][139][140][141][142]. Bozhinova [143] reported that the application of the microbial inoculant Europlus ® and the protein hydrolysate (PH) Trainer ® increased the yield of tobacco by 5.5% and 6.7%, respectively, in comparison with untreated plants.…”
Section: Mechanisms Of Microbial Biostimulant Actionmentioning
confidence: 99%